O-Vinylphosphonylated Salicylaldehydes as Aldo-Vinyl Bifunctional Building Blocks for anti-3,4-Disubstituted Phosphadihydrocoumarins - Wang, Qinghe; Kong, Dulin; Huang, Tiao; Wu, Mingshu (Synthesis, 2019)
An efficient synthetic strategy for anti-3,4-disubstituted phosphadihydrocoumarin compounds has been established by tandem aza-Michael–aldol-like annulations of tetrahydroisoquinolines with O-vinylphosphonylated salicylaldehydes as an aldo-vinyl bifunctional building block. This conversion was characterized by ‘green’ properties such as a step- and atom-economy, catalyst-free conditions, highly anti-selectivity, and readily available starting materials.
Keywords: benzo[e][1,2]oxaphosphinine; β-amino-β′-hydroxyalkylphosphonate; phosphadihydrocoumarin; tetrahydroisoquinoline; intermolecular annulation